Internet Society and Global Culture. Revision of Interdisciplinary Project at Opole University of Technology - Анна Райчел; Мілена Й. Єнджеєвська (Історико-політичні проблеми сучасного світу)
An interdisciplinary project “Internet society and global culture” was conducted by the Faculty of Economics and Management of the Opole University of Technology, in 2012-2020. The idea lead to exam the relationships between various areas of global culture inscribed in virtual space. Researchers considered human functioning regarding online safety, risks and benefits of using the Internet, exclusion of “offline people” and especially young users. Different institutions were reviewed: schools, libraries, churches, banks, shops, etc. The result of the joint meetings was the creation of six monographs: “Internet society and global culture. Legal and cultural aspects of human functioning in virtual reality”, “Internet society and global culture”, “Church on the Internet – Internet in the Church: Internet society and global culture”, “Internet and modern economy”, “Internet society and global culture. Young user on the web. Part 2”, “Internet society and global culture. New media in education as a challenge of the 21st century”. The project was directed primarily to young people for whom the virtual world has become a permanent part of their life, study and work. Globalization is an irreversible process that brings benefits but also brings threats (e.g. climate change). It was very important that teachers, entrepreneurs and representatives of public administration participated in the project together with the students. The topic has become particularly important in connection with the Covid-19 pandemic and its limitations.